Pooled population pharmacokinetic model of imipenem in plasma and the lung epithelial lining fluid. (1st April 2016) - van Hasselt, J. G. Coen; Rizk, Matthew L.; Lala, Mallika; Chavez‐Eng, Cynthia; Visser, Sandra A. G.; Kerbusch, Thomas; Danhof, Meindert; Rao, Gauri; van der Graaf, Piet H.
Abstract : Aims: Several clinical trials have confirmed the therapeutic benefit of imipenem for treatment of lung infections. There is however no knowledge of the penetration of imipenem into the lung epithelial lining fluid (ELF), the site of action relevant for lung infections. Furthermore, although the plasma pharmacokinetics (PK) of imipenem has been widely studied, most studies have been based on selected patient groups. The aim of this analysis was to characterize imipenem plasma PK across populations and to quantify imipenem ELF penetration. Methods: A population model for imipenem plasma PK was developed using data obtained from healthy volunteers, elderly subjects and subjects with renal impairment, in order to identify predictors for inter‐individual variability (IIV) of imipenem PK. Subsequently, a clinical study which measured plasma and ELF concentrations of imipenem was included in order to quantify lung penetration. Results: A two compartmental model best described the plasma PK of imipenem. Creatinine clearance and body weight were included as subject characteristics predictive for IIV on clearance. Typical estimates for clearance, central and peripheral volume, and inter‐compartmental clearance were 11.5 l h –1, 9.37 l, 6.41 l, 13.7 l h –1, respectively (relative standard error (RSE) <8%). The distribution of imipenem into ELF was described using a time‐independent penetration coefficient of 0.44 (RSE 14%). Conclusion: The identified lung penetration coefficient confirms the clinical relevance of imipenem for treatment of lung infections, while the population PK model provided insights into predictors of IIV for imipenem PK and may be of relevance to support dose optimization in various subject groups.